Nutritional and Therapeutic Potential of Allium Vegetables - Kant Upadhyay, Ravi (Journal of Nutritional Therapeutics, 2023)
Allium vegetables are highly nutritional, its dietary use improves digestion and mental health and lower down cholesterol level. Use of onions, garlic, scallions, chives and leeks show therapeutic efficacy against cardiovascular disease, hyperglycemia, and stomach cancer, Onions contain allylsulfides and flavonoids particularly quercetin that is an important anti-oxidative and reduces hepatocytes apoptosis in streptozotocin-induced diabetic rat. Steroid saponins and sapogenins present in garlic bulbs are used to prepare soft soaps. β-chlorogenin is a characteristic steroid sapogenin from garlic that is used for skin ointment and as a shiner. Both garlic paste and soft garlic preparations are used for flavoring the food items. Garlic products that contain the most safe, effective, stable, and odorless components are the most valuable as dietary supplements. Garlic also contains non sulfur compounds such as steroid saponins. Alliums showed antimicrobial, antithrombotic, antitumor, anti-hyperlipidaemic, antiarthritic, anti-hyperglycemic anticarcinogenic potential. Allium vegetables contain organosulfur compounds, including DATS, diallyl disulfide (DADS), ajoene, and S-allylmercaptocysteine (SAMC), have been found to induce cell cycle arrest in cancer cells. Alliums have great ethnomedicinal importance as these are used as native remedies against wide spectrum of diseases including diabetes. Allium origin natural products are of great therapeutic and dietary use. These are most preferred items used by nutritionists, physicians, food technologists, food chemists. Green allium vegetables are good source of natural pharmaceutics which are good for health and act against nutritionally induced acute and chronic diseases. Their possible inclusion in diets could explore new therapeutic avenues to enhance immunity against diseases.